Upaya Guru dalam Meningkatkan Keterampilan Tajwid Siswa melalui Metode Talaqqi pada Mata Pelajaran PAI di SD Negeri 57 Buton - Fathur Rahmat; Rusli Rusli; Jufri Jufri (Universitas Palan, 2026)
This study aims to determine the implementation process of the talaqqi method in teaching tajwid in Islamic Religious Education subjects and the obstacles encountered in its implementation at SD Negeri 57 Buton. This research used a qualitative approach with descriptive research type. The subjects of the study were Islamic Religious Education teachers and 23 fifth grade students. Data collection techniques included observation, interviews, and documentation. Data analysis techniques consisted of data reduction, data display, and conclusion drawing. The results showed that the implementation of the talaqqi method was carried out through several stages: the teacher first demonstrated the correct recitation of the Qur'an, students listened carefully, and then students imitated the recitation both collectively and individually. The talaqqi method helps teachers directly correct students' recitation mistakes, thereby improving students' tajwid skills. The obstacles found include differences in students' Qur'an reading abilities, limited learning time, and lack of practice at home. To overcome these obstacles, the teacher provided additional guidance and motivated students to practice reading the Qur'an more frequently.